Advantage play : technologies that changed sporting history - Haake, Steve, ....- (Edinburgh : Arena Sport, 2018)
Advantage Play tells the dramatic stories of the key technological breakthroughs in four thousand years of sporting history used to gain an advantage in sport. Novel materials are never far away: rubber for rugby and tennis balls, carbon fibre for bikes and prosthetics, polyurethane for swimsuits. Breakthroughs crop up throughout history, not just for modern football boots but for the javelin of the ancient Greeks and even the original starting line at Olympia. Our obsession with sporting data is not new although our methods of collecting it is: phones, sensors and monitors. Together, these breakthroughs reveal that the way we design sports equipment has always been much the same. Rather than being a new thing, sports technology is actually as old as civilisation. Where will it all end? All current track and field events at the modern Olympic Games will reach their limit within a generation. With his 30 years as a sports engineer, Steve Haake shows that in a world where top performances are static, where we've found all the best athletes and deployed the best coaching methods, the one thing that might distinguish the winners from the losers is new technology.
Sport ; geschiedenis